STRATEGI PEMBELAJARAN KOLABORATIF TERINTEGRASI KECERDASAN MAJEMUK DAN HUBUNGANNYA DENGAN KECERDASAN LOGIKA MATEMATIKA DAN PEMAHAMAN KONSEP PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN - Hening Pertiwi; Atiek Winarti; Mahdian Mahdian (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2017)
Abstract. This study aimed to determine the effectiveness of collaborative learning strategies integrated of multiple intelligences to improve the intelligence of mathematical logic and the comprehension of concepts of experimental class in SMA Negeri 5 Banjarmasin. The research conducted to the experimental research method through pretest-posttest control group design. Class XI IPA 1 students as experiment group and XI IPA 4 students as control group. The control group used conventional methods, and then the experimental group implemented thru collaborative learning strategy integrated to multiple intelligences. Data collection used test and non-test techniques namely observation and multiple intelligence questionnaires. Data analysis technique used t-test and descriptive analysis. The result showed is that the collaborative learning strategies integrated of multiple intelligence effective to mathematical logic intelligence and concept comprehension of experimental group students compared with control group.Keywords: collaborative, multiple intelligences, mathematical logic,comprehension of concepts, solubility and solubility product.